Pengembangan Desain Map Rekam Medis sebagai Program Magang Mahasiswa di Puskesmas Mojolangu - Abdullah , Rizky; Wijaya, Avid (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
The Community Health Center (Puskesmas), as the foundation of public health services, requires improved efficiency in medical record management to enhance service quality. The optimal design of medical record maps is a key element in establishing a structured and easily accessible patient information recording system. The main objective of this community service is to enhance the quality and efficiency of healthcare services at Puskesmas Mojolangu through the development of medical record map designs. The methodology employed is internship, where students are actively involved in the development of medical record map designs at Puskesmas Mojolangu. The steps involve user needs analysis, map design development, implementation, and evaluation. Students and Supervisors coordinate and interact with healthcare professionals and administrative staff at the health center to gather constructive input and feedback. The outcome of this community service is the development of more efficient and structured medical record map designs. The new design is expected to improve information accessibility, expedite data retrieval processes, and reduce the risk of errors in recording. The implementation of the new medical record map design is also anticipated to have a positive impact on inter-unit coordination at Puskesmas Mojolangu. The students' contribution as change agents in the development of the medical record system has provided innovative solutions to overcome challenges faced by the health center in managing patient health information. The conclusion drawn from this activity indicates that involving internship students in the development of medical record map designs can be a positive step in enhancing primary healthcare services.